Image encryption through web application using AES / Aina Nadhrah Mohd Zaid - Mohd Zaid, Aina Nadhrah (2020)
A few decades ago, the advent of informational technology (the Internet) led to many changes in the way information is disseminated and shared among people, between countries and throughout the world. Years afterwards, the problem of the "theft" of information has emerged globally. Specialists in the area of information security are curious to see if it can be remedied. It is now clear that security of knowledge is the panacea, despite the prevalence of certain newly discovered methods of cryptanalysis. Thus, this project is proposed in order to create a secure web application for people to encrypt their image. The application is user friendly for everyone to use it daily without much hustle. This project will use Laravel and XAMPP to create the web application and the encryption process. User will upload their image for encryption and decryption through the web application and download their image whenever they need it.